Participative Villager Empowerment for Socio-Economic Development - M. Yassin, Sulaiman; Muhammad, Ahmad (Universiti Putra Malaysia Press, 1993)
Development approaches that allows for greater participation of the rural poor and that are sustainable in nature have long been examined, tested and further researched. In Malaysia, such a project approach has been tested in four villages with a focus on empowering village communities with social and technical skills. A consultative stance is adopted by the development agents who encouraged the villagers to decide on their own courses of action. In the project villages, socio-economic activities ranging from educational to agricultural and livestock components were successful. The positive results indicated that the poor can be empowered to develop their own ideas through human resource development and participatory approach. Project activities initiated in this manner were found to more sustainable.